2020
DOI: 10.1101/2020.06.10.144642
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultrastructural analysis of SARS-CoV-2 interactions with the host cell via high resolution scanning electron microscopy

Abstract: HighlightsWe used high resolution scanning electron microscopy to investigate Vero cells infected with SARS-CoV-2 at 2 and 48 hours post-infection. The central conclusions of this work include:• Infected cells display polarization of their cytosol forming a restricted viroplasm-like zone dedicated to virus production and morphogenesis.• This is the first demonstration of SARS-CoV-2 attachment by scanning electron microscopy.• This is the first scanning electron microscopy images of the interior of SARS-CoV-2 i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
28
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 37 publications
(24 reference statements)
14
28
1
Order By: Relevance
“…The SARS‐CoV‐2 SP‐induced LVCVs were further explored in our previous studies using SEM to inspect the infected cell's interior. Consistent with them, the electron tomography carried in the present work allowed the finding of virus particles of different sizes although presenting similar shapes (Figure 5 and Supplemental Material 1), previous corroborating data obtained by SEM and TEM (Caldas et al., 2020b; Zhao et al., 2020). Studies on cryo‐electron tomography showed that SARS‐CoV‐2 acquires its envelope, while budding through the LVCVs, which already display the S protein adhered to their internal face (Figure 3D) (Klein et al., 2020).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The SARS‐CoV‐2 SP‐induced LVCVs were further explored in our previous studies using SEM to inspect the infected cell's interior. Consistent with them, the electron tomography carried in the present work allowed the finding of virus particles of different sizes although presenting similar shapes (Figure 5 and Supplemental Material 1), previous corroborating data obtained by SEM and TEM (Caldas et al., 2020b; Zhao et al., 2020). Studies on cryo‐electron tomography showed that SARS‐CoV‐2 acquires its envelope, while budding through the LVCVs, which already display the S protein adhered to their internal face (Figure 3D) (Klein et al., 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Since our previous study, we investigated the SARS‐CoV‐2 SP viroplasm by SEM (Caldas et al., 2020b); the membrane structures and compartments involved in the replication and morphogenesis of this virus were now studied by TEM herein. Therefore, this work contributes to understanding the interaction mechanisms between SARS‐CoV‐2 and the host cells, taking into account the general morphological alterations, the recruitment of organelles and cell components in the context of the intense membrane remodelling that takes place during infection.…”
Section: Discussionmentioning
confidence: 99%
“…τ-STED microscopy demonstrates that fluorescent particles on the cell membrane were composed by single viruses, with ∼100-130 mm size, as well as very small clusters of about 2-3 virions (Figure 3, inset). These findings were in agreement with a previous electron microscopy study, which showed at 6h membrane-attached single and pair of wild-type SARS-CoV-2 viruses, with poor cell internalization 41,42 . The strong interaction of B.1.1.7 with cells at ~1h detected by microscopy was consistent with the short 1h exposure able to activate strong viral production after one day, at odds with the phenotype observed for B.1 (Figure 2b).…”
Section: Visualization Of Virus During Entry and Egresssupporting
confidence: 93%
“…We suggest that this resembles the particle clustering by host defense protein BST-2 as it was observed for human coronavirus229E and quantified in HeLa cells by Wang et al [35]. However, the metal coating applied by Wang et al is clearly visible at high resolution in the SEM images as a rough layer on the cell membrane and hiding the true topography [24], [24], [36]. In contrast, the HIM images presented here not only allow for the quantification of particles and clusters, but also enable an unveiled view on the interaction of virus particles with the cell membrane.…”
Section: Resultssupporting
confidence: 63%